A novel self-expanding primarily bioabsorbable braided flow-diverting stent for aneurysms: initial safety results. (27th November 2019) - Jamshidi, Mehdi; Rajabian, Mahmoud; Avery, Michael B; Sundararaj, Uttandaraman; Ronsky, Janet; Belanger, Brooke; Wong, John H; Mitha, Alim P
Abstract : Introduction: The advent of metal flow-diverting stents has provided neurointerventionalists with an option for treating aneurysms without requiring manipulations within the aneurysm sac. The large amount of metal in these stents, however, can lead to early and late thrombotic complications, and thus requires long-term antiplatelet agents. Bioabsorbable stents have been postulated to mitigate the risk of these complications. Here we present early data on the first self-expandable primarily bioabsorbable stent for aneurysms. Methods: Braided stents were developed using poly-L-lactic acid fibers with material surface area similar to metal flow diverters. Crush resistance force, hemolysis, and thrombogenicity were determined and compared with existing commercial devices. Stents were deployed in infra-renal rabbit aortas to determine angiographic side branch patency and to study neointima formation for a 1-month follow-up period. Results: Crush resistance force was determined to be on the order of existing commercial devices. Hemolytic behavior was similar to existing metal devices, and thrombogenicity was lower than metal flow-diverting stents. A smooth neointimal layer was found over the absorbable stent surface and all covered side branches were patent at follow-up. Conclusion: The design of self-expanding primarily bioabsorbable flow-diverting stents is possible, and preliminary safety data is consistent with a favorable profile in terms of mechanical behavior, hemocompatibility, side branch patency, and histological effects. Additional in vitro and long-term in vivo studies are in progress and will help determine aneurysm occlusion rates and absorption characteristics of the stent.